PELATIHAN HERO UNTUK MENINGKATKAN KESEJAHTERAAN PSIKOLOGIS REMAJA PANTI ASUHAN - Alfinuha, Setyani; Hadi, Bagus H; Sinambela, Frikson Cristian (Jurnal Psikologi Teori dan Terapan, 2019)
This study aims to improve the psychological well-being of adolescent orphanages through psychological capital training. The psychological capital aspects provided in this training were hope, self-efficacy, resilience, and optimism (HERO). The material was conveyed using the experiential learning approach with lecturing, audio-visual method, written assignments, discussion, plays, and reflection. The research participants were 20 teenagers from Pelita orphanages (14-18 years) at Surabaya. The design chosen was one-group pretest-posttest design. Data were collected using The Ryff?s Scale of Psychological Well-being and analyzed using paired sample t-test with the help of SPSS 16.0 version. The result shows that there is a significant difference in participants? psychological well-being between before and after training was given. This proves that HERO training in this study is able to improve the psychological well-being of adolescent orphanages.Keywords: psychological well-being, psychological capital, teenage orphanages Abstrak: Penelitian ini bertujuan untuk meningkatkan kesejahteraan psikologis remaja yang tinggal di Panti Asuhan Pelita melalui pelatihan modal psikologis. Aspek modal psikologis yang diberikan pada pelatihan ini yaitu hope, self-efficacy, resilience, dan optimism (HERO). Materi disampaikan menggunakan konsep experiential learning dengan metode lecturing, audio-visual, tugas tertulis, dikusi, permainan, dan refleksi. Partisipan penelitian yaitu 20 remaja (14 ? 18 tahun). Desain yang dipilih adalah one-group pretest-posttest design. Variabel kesejahteraan psikologis diukur menggunakan The Ryff Scale of Psychological Well-being. Analisis data kuantitatif menunjukkan perbedaan signifikan sebelum dan sesudah pelatihan diberikan. Hal ini membuktikan bahwa tingkat kesejahteraan psikologis meningkat setelah diberi pelatihan HERO.